1982
DOI: 10.1073/pnas.79.24.7734
|View full text |Cite
|
Sign up to set email alerts
|

Excessive mineralization with growth plate closure in rats on chronic warfarin treatment.

Abstract: Rats maintained for 8 months on a level of warfarin sufficient to decrease the vitamin K-dependent protein of bone (bone Gla protein) to 2% ofnormal have an excessive mineralization disorder characterized by complete fusion of the proximal tibial growth plate and cessation of longitudinal growth. The general features of this abnormality resemble the fetal warfarin syndrome in humans, a disorder also characterized by excessive mineralization of the growth plate. These excessive mineralization disorders may be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
104
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(107 citation statements)
references
References 21 publications
3
104
0
Order By: Relevance
“…In laboratory animals, ectopic calcifications were observed in mice ApoE Ϫ/Ϫ treated by warfarin (20). Similarly, OC depletion in bone was observed consecutively to the use of warfarin (22,23). Nevertheless, the dose of warfarin used in both studies was completely disproportionate compared with the therapeutic dose used in human medicine.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…In laboratory animals, ectopic calcifications were observed in mice ApoE Ϫ/Ϫ treated by warfarin (20). Similarly, OC depletion in bone was observed consecutively to the use of warfarin (22,23). Nevertheless, the dose of warfarin used in both studies was completely disproportionate compared with the therapeutic dose used in human medicine.…”
mentioning
confidence: 94%
“…In other soft tissues known to also express MGP at a high rate, no calcification was observed in the different studies. When rats were treated with a warfarin dose given once every 24 h, a complete absence of artery calcification was noted (22,23,34,35). Some of these studies described a depletion of OC in bone consecutively to the inhibition of ␥-carboxylation of this VKDP (22,23,35,36).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, vitamin K is an important regulator of bone and cartilage mineralization. Vitamin K also regulates growth plate cartilage calcification, as revealed by effects of vitamin K antagonism by warfarin (6)(7)(8)(9)(10). Genetic deficiencies of MGP in humans and mice have been linked to skeletal abnormalities, including premature epiphyseal calcification and shortening of long limb bones, reflecting endochondral bone formation (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Since then, many in vitro and in vivo experiments have shown that VKAs induce vitamin K deficiency, which has been unequivocally related to increased mineralization of several tissues, particularly in the vascular tree and skeletal elements. Rats treated with warfarin presented extensive vascular calcification which could be inhibited by simultaneous treatments with vitamin K [28][29][30]. Furthermore, vitamin K was shown to induce a regression of preformed warfarin-induced vascular calcifications, with restoration of arterial distensibility [31].…”
Section: Vitamin K-antagonists As Indicators Of Vitamin K Importance mentioning
confidence: 99%